THE IMPLEMENTATION OF HOT CHAIR GAME IN TEACHING SPEAKING SKILL AT THE SECOND SEMESTER OF ENGLISH DEPARTMENT STUDENTS - Arif, Ummi Qalsum (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
ABSTRACT Speaking is a crucial component of English language learning in EFL contexts, yet many university students encounter difficulties in expressing their ideas orally due to limited vocabulary, low confidence, and speaking anxiety. This study focuses on the use of the Hot Chair Game as an interactive learning strategy to enhance the speaking skills of second-semester students in the English Education Study Program at IKTL. The research employed a descriptive qualitative design. Data were collected through classroom observations, field notes, and students’ reflective written responses over four instructional meetings. Data were analyzed through descriptive qualitative analysis focusing on patterns of speaking performance, classroom interaction, and learning engagement. The findings reveal that the Hot Chair Game resulted in observable improvements in students’ vocabulary recall, speaking fluency, and willingness to participate in oral activities. In addition, students demonstrated increased confidence and reduced speaking anxiety, as indicated by more frequent voluntary responses and sustained oral interaction during classroom activities. Although some challenges remained, such as limited vocabulary mastery and occasional reliance on their native language, students gradually adapted to English-speaking situations. Overall, the results indicate that the Hot Chair Game is an effective and engaging alternative strategy for improving speaking skills in higher education, as it fosters active participation, reduces anxiety, and enhances communicative competence in EFL classrooms. ABSTRAK Speaking merupakan komponen penting dalam pembelajaran Bahasa Inggris dalam konteks EFL, namun banyak mahasiswa mengalami kesulitan dalam mengekspresikan ide secara lisan akibat keterbatasan kosakata, rendahnya rasa percaya diri, dan kecemasan berbicara. Penelitian ini berfokus pada penggunaan Hot Chair Game sebagai strategi pembelajaran interaktif untuk meningkatkan keterampilan berbicara mahasiswa semester dua Program Studi Pendidikan Bahasa Inggris di IKTL. Penelitian ini menggunakan desain deskriptif kualitatif. Data dikumpulkan melalui observasi kelas, catatan lapangan, dan respon reflektif tertulis mahasiswa selama empat kali pertemuan pembelajaran. Data dianalisis secara deskriptif kualitatif dengan fokus pada pola kemampuan berbicara mahasiswa, interaksi kelas, dan keterlibatan belajar selama proses pembelajaran. Hasil penelitian menunjukkan bahwa penerapan Hot Chair Game menghasilkan peningkatan dalam kemampuan mengingat kosakata, kelancaran berbicara, serta kemauan mahasiswa untuk berpartisipasi dalam aktivitas lisan. Selain itu, mahasiswa menunjukkan peningkatan rasa percaya diri dan penurunan kecemasan berbicara, yang ditandai dengan meningkatnya respon sukarela serta interaksi lisan yang lebih berkelanjutan di kelas. Meskipun masih ditemukan beberapa kendala seperti keterbatasan kosakata dan penggunaan bahasa ibu secara sesekali, mahasiswa secara bertahap mampu beradaptasi dalam situasi berbahasa Inggris. Secara keseluruhan, hasil penelitian menunjukkan bahwa Hot Chair Game merupakan strategi alternatif yang efektif dan menarik dalam meningkatkan keterampilan berbicara di perguruan tinggi karena mampu mendorong partisipasi aktif, mengurangi kecemasan, dan meningkatkan kompetensi komunikatif dalam konteks EFL.